Desarrollo de tecnología para la valorización de los dsechos agroindustriales - La red en el campo de la utilización de desechos de frutas. - Durán Cavaria, M.; Moya, M.; Starbird, R.; Umaña, E.; Jiménez, G.; Nikolaeva, S. (Corporación Colombiana de Investigación Agropecuaria - CORPOICA, 2018)
The CYTED was created in 1984 by the presidents of Spain, Portugal and Latinamerica as a cooperation Program in the field of Science and Technology. Technology, agroindustrial, food, forest, materials, acuiculture, energy and biomass are fields very important in the program integrated in projects and networks. The network Tecnologías para la Valorización de los Desechos Agroindustriales (IV.F) bunch up researchers from fifteen countries who are interested in the evaluation of agroindustrial wastes and work together in order to develop new technologies to minimize the impact of agroindustrial activity. The network has worked with some fruit biowaste projects, like pineapple, banana and orange. In Latin America the network has projects with international cooperation. Costa Rica is researching now a project about composite materials with rachis of banana, it tríes to use the biomass and technology by greater added value of biowastes.